PEMBERDAYAAN BERBASIS MASJID MELALUI PROGRAM URBAN FARMING - Savitri, Fania Mutiara (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This study aims to (1) determine the implementation of mosque-based community empowerment strategies through the Urban Farming program at Al Fattah mosque Semarang and (2) knowing the supporting and inhibiting factors of mosque-based community empowerment in the Urban Farming program through the Urban Farming program at the Al Fattah mosque, Semarang. This study uses the PLA (Participatory Learning and Action) method. The results of this study indicate that (1) the implementation of a mosque-based community empowerment strategy in semarang Village uses Adult Education Strategy (POD) and PLA (Participatory Learning and Action) or Learning by doing. In this PLA strategy, empowerment partners gain a lot of knowledge based on their daily experiences which are shaped from their living environment. (2) the supporting factors for mosque-based community empowerment are based on the internal aspects of this empowerment having advantages from the social, economic, psychological and ecological aspects, namely having very high solidarity, enthusiasm for business development in agriculture and being able to maintain a healthier and more environmentally friendly environment. clean while the inhibiting factor comes from the external aspect, it can be seen that the mastery of Urban Farming technology innovation is still minimal so it requires more intensive assistance.